The reliability of the Greek version of the Communicative Effectiveness Index (CETI-GR) for people with chronic aphasia in Cyprus - Christodoulou, Maria (My University, 2024)
Functional communication assessment in people with aphasia (PWA) is crucial for designing personalized interventions. Adapting assessment tools, like The Communicative Effectiveness Index (CETI) into Greek, is essential for functional goal setting in aphasia rehabilitation. This thesis aimed to examine the reliability of the Greek version of the CETI (CETI – GR). The CETI was adapted and back-translated into Greek. Its reliability was tested through test-retest and interrater measures, and internal consistency analyses. The sample included 60 participants, 30 PWA and 30 respective carers. Statistical analyses, including Cronbach's alpha, were utilized to assess internal consistency. The Greek adaptation of the CETI (CETI-GR) demonstrated excellent internal consistency (α = 0.95), high test-retest reliability (ICC = 0.88), and excellent interrater reliability (ICC ≥ 0.93). The Greek version of the CETI (CETI-GR) is a reliable tool for assessing functional communication in people with chronic aphasia. Its adaptation into Greek provides Greek-speaking speech and language therapist with a valuable resource for chronic aphasia assessment and rehabilitation, facilitating person-centered care and enhancing the quality of life for PWA and their carers.
Keywords: CETI-GR; people with aphasia; tool reliability; functional communication; CETI-GR; άτομα με αφασία; αξιοπιστία εργαλείου; λειτουργική επικοινωνία